2008
DOI: 10.1080/10803548.2008.11076767
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Mental Stress and Reactions in Heart Rate Variability—A Pilot Study Among Employees of an Electronics Company

Abstract: In this study perceived mental stress during occupational work was compared to heart rate variability (HRV) using a traditional questionnaire and a novel wristop heart rate monitor with related software. (r = -.73 and r = -.60, respectively). The analysis shows that as the RMSSD and TINN value differences increase from night to morning, the stress decreases. The aim was to find HRV parameters useful for mental stress detection. We found the highest correlation between perceived mental stress with the differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(74 citation statements)
references
References 27 publications
(31 reference statements)
6
66
1
1
Order By: Relevance
“…Hjortskov et al showed that subjective mental stress in computer work is related to changes in HRV between rest and work periods [13]. Orsila et al showed that the level of mental stress in occupational work has a negative correlation with certain HRV features, i.e., triangular interpolation of rhythm-to-rhythm (RR) interval histogram (TINN) and RMSSD [14]. Bailon et al proposed a method for estimating mental stress during exercise using HRV and respiration features [15].…”
Section: Introductionmentioning
confidence: 99%
“…Hjortskov et al showed that subjective mental stress in computer work is related to changes in HRV between rest and work periods [13]. Orsila et al showed that the level of mental stress in occupational work has a negative correlation with certain HRV features, i.e., triangular interpolation of rhythm-to-rhythm (RR) interval histogram (TINN) and RMSSD [14]. Bailon et al proposed a method for estimating mental stress during exercise using HRV and respiration features [15].…”
Section: Introductionmentioning
confidence: 99%
“…Directly or indirectly stress is linked to work related illness [20]. Precisely this reflects in diurnal variation of HRV (21).HRV shows wide variation in normal populations, as autonomic outflows are labile not constant. Age, emotion, time of day, posture all influence HRV [22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…[7,29,39]). It correlates well with salivary measurements of cortisol and alpha-amylase as has been shown in [22].…”
Section: Physiological Indicators For Stressmentioning
confidence: 99%